Innovation Cluster Of Pedagogical Education As Mechanisms Of Coordinating Activities Of Inclusive Education Participants (Eurasian Journal of Research, Development and Innovation, 2024)
In this article, the organization of inclusive education with the help of pedagogical educational innovation cluster, the role of neighborhood, family, school in the lives of children who need special support, education, and adaptation to society, with the help of pedagogical educational cluster we can learn about the coordination of the activities of the participants of inclusive education and the development of mechanisms.